2007
DOI: 10.1007/s00442-007-0658-6
|View full text |Cite
|
Sign up to set email alerts
|

Extreme weather change and the dynamics of oviposition behavior in the pipevine swallowtail, Battus philenor

Abstract: Prospects of global increases in extreme weather change provide incentive to examine how such change influences animal behavior, for example, behavior associated with resource use. In this study, we examined how oviposition behavior in a southern Arizona population of pipevine swallowtails (Battus philenor L.) responded to changes in their Aristolochia host resource and vegetative background caused by the North American monsoon system. Summer monsoon rains resulted in a flush of non-host vegetation and a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…, Fordyce , Klitzke and Brown , Sime , Papaj et al. ). Troidine swallowtails are predominantly tropical and subtropical, occurring in lowland forests of Central and South America, with two genera recognized in the New World, Battus and Parides (Weintraub ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Fordyce , Klitzke and Brown , Sime , Papaj et al. ). Troidine swallowtails are predominantly tropical and subtropical, occurring in lowland forests of Central and South America, with two genera recognized in the New World, Battus and Parides (Weintraub ).…”
Section: Introductionmentioning
confidence: 99%
“…One group of butterflies that sequester chemical defenses from their host plants are swallowtail butterflies in the Troidini (Papilionidae) tribe (Nishida et al 1993, Fordyce 2000, Klitzke and Brown 2000, Sime 2002, Papaj et al 2007). Troidine swallowtails are predominantly tropical and subtropical, occurring in lowland forests of Central and South America, with two genera recognized in the New World, Battus and Parides (Weintraub 1995).…”
Section: Introductionmentioning
confidence: 99%
“…These may prove to be important drivers of climate-related impacts on species populations (Ehrlich et al 1980; Morecroft et al 2002; Jentsch et al 2008; Piessens et al 2009). The impact of weather extremes may directly affect populations by increased mortality (Mercader and Scriber 2008) and reduced reproduction (Papaj et al 2007) or indirectly by changes in host plant availability (Piessens et al 2009) or changing rates of parasitism and predation (Dennis 1993; Menéndez et al 2008; Parmesan et al 2000). …”
Section: Introductionmentioning
confidence: 99%
“…With an eye to the potential impacts of climate change, ecological research has increasingly focused on climatic variability (Wang & Dillon, ; Vázquez et al ., ; Boyd et al ., ) and extreme events (Jentsch et al ., ; Smith, ; Knapp et al ., ; Bailey & van de Pol, ). Studies have demonstrated the implications of climatic variance and extremes for behavior (Rubenstein, ; Papaj et al ., ; Frick et al ., ), demography (Sæther, ; Langin et al ., ; Jónsson et al ., ), distributions (Reside et al ., ; Bateman et al ., ), community composition (Albright et al ., ; Hoover et al ., ), mass mortality events (McKechnie & Wolf, ; Anderegg et al ., ), fire dynamics (Westerling et al ., ; Littell et al ., ; Abatzoglou & Kolden, ), carbon cycling (Frank et al ., ), and invasive species (Vilà et al ., ; Diez et al ., ; Sheppard et al ., ), among others. The temporal scale at which extreme events are defined varies from daily to multidecadal timescales, with the timescale of interest dependent on the impact of interest (e.g., heat‐induced mortality versus annual gross primary productivity).…”
Section: Dimensions Of Climate Change and Their Representation Withinmentioning
confidence: 99%